Comparison of high-intensity focused ultrasound ablation and uterine artery embolization in the management of cervical pregnancy - Li, Waixing; Gan, Xiaoli; Kashyap, Nidhi; Zou, Lingxiao; Zhang, Aiqian; Xu, Dabao (Frontiers in Medicine, 2022)
Background: Cervical pregnancy (CP) is an uncommon type of ectopic pregnancy with a rising risk to life. Currently, there is no universal protocol for the safe and effective management of CP. This study aimed to investigate the clinical efficacy of high-intensity focused ultrasound ablation (HIFU) versus uterine artery embolization (UAE) in the management of CP to develop a standard for the treatment of CP. Methods: From January 2015 to October 2021, 36 patients with CP were diagnosed, treated, and followed-up at the Department of Gynecology of Third Xiangya Hospital of Central South University. Eleven patients were treated with HIFU followed by suction curettage under hysteroscopic guidance and 25 patients were treated with UAE followed by suction curettage under hysteroscopic guidance. Medical records and pregnancy outcomes were retrospectively analyzed. Results: Compared to the UAE group, the HIFU group had a shorter interval time (1.5±0.21 days vs 2.6±0.26 days), shorter duration of hospitalization (5.5±0.31 days vs 6.6±0.21 days), shorter recovery time of menstruation (30.6±7.09 days vs 36.9±5.54 days), fewer adverse reactions (0/11 vs 9/25), and fewer postoperative complications (1/11 vs 8/25). There were no significant differences in age, gravidity, parity, abortion, gestational age, cardiac pulsation, admission symptoms, hemoglobin level, largest diameter of the sac/mass, serum hCG level at admission, hospitalization expenses, hospitalization days, blood loss during curettage, degree of hCG decline, residue after curettage, fertility requirement, and pregnancy outcomes. Conclusion: Both HIFU and UAE are safe and effective in the treatment of patients with CP. Compared to UAE, HIFU treatment for CP is a safer and more effective therapeutic schedule owing to the advantages of being more minimally invasive, shorter interval time, shorter hospitalization days and recovery time of menstruation, fewer adverse reactions, and fewer postoperative complications.